Numerical simulation for magnetohydrodynamic three dimensional flow of Casson nanofluid with convective boundary conditions and thermal radiation. Issue 8 (6th November 2017) - Gupta, Sumit; Sharma, Kalpna
Abstract : Purpose: The purpose of this study is to analyze magnetohydrodynamic three-dimensional flow of Casson nanofluid over a stretching sheet in presence of thermophoresis and Brownian motion effects. In contrast, the convective surface boundary conditions with the effects of radiation are applied. Design/methodology/approach: The governing partial differential equations are transformed into highly nonlinear coupled ordinary differential equations consisting of the momentum, energy and nanoparticle concentration via suitable similarity transformations, which are then solved the using optimal homotopy analysis method (OHAM) a Mathematica Package BVPh2.0. Findings: The influence of emerging physical flow parameters on fluid velocity component, temperature distribution and nanoparticle concentration are discussed in detail. Also, an OHAM solution demonstrates very good correlation with those obtained in the previously published results. It is noticed that OHAM can overcome the earlier restriction, assumptions and limitation of traditional perturbation method. The main advantage of this method is that OHAM can be applied directly to nonlinear differential equations without using linearization and round-off errors, and therefore, it cannot be affected by error associated to discretization. Originality/value: Here the approximate solutions are compared with the numerical results published in earlier work.